2020
DOI: 10.1891/jcpsy-d-19-00015
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Mind-Wandering and Cognitive Fusion Through Mindfulness Group Therapy for Depression and Anxiety

Abstract: The mechanisms of efficacy in mindfulness-based interventions for depression and anxiety are not fully understood. To clarify these mechanisms, we tested the hypotheses that mind-wandering, daydreaming, cognitive fusion, and experiential avoidance will decrease through mindfulness group therapy, and this decrease will correlate with improvements in depression and anxiety. Participants self-reported depression and/or anxiety (N = 28) took part in an 8-week mindfulness group therapy program. They were assessed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In addition, according to the Attentional Control Theory of anxiety (Eysenck et al, 2007), anxiety tends to impair attention control; according to the Control Failure Model of mind wandering, failure of attention control leads to greater propensity to mind wander (McVay & Kane, 2010; Robison et al, 2017); therefore, individuals with trait anxiety may have increased mind wandering. Moreover, an intervention program also showed that decreases in mind wandering were moderately correlated with improvements in anxiety (Takahashi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, according to the Attentional Control Theory of anxiety (Eysenck et al, 2007), anxiety tends to impair attention control; according to the Control Failure Model of mind wandering, failure of attention control leads to greater propensity to mind wander (McVay & Kane, 2010; Robison et al, 2017); therefore, individuals with trait anxiety may have increased mind wandering. Moreover, an intervention program also showed that decreases in mind wandering were moderately correlated with improvements in anxiety (Takahashi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…There is a strong association between depressive symptoms and cognitive fusion, which is an important and independent predictor of depressive symptoms (Pinto-Gouveia et al, 2020). Negative emotions such as depression and anxiety can be moderately improved if an individual's cognitive fusion is reduced (Takahashi et al, 2020). New mothers, because of putting work aside, experiencing sleep deprivation, providing newborn care and transitioning to parenthood, are much more likely to feel overwhelmed and subsequently depressed (Iliadis et al, 2017); they are sensitive to stress and may develop personal vulnerability.…”
Section: What Does This Paper Contribute To the Wider Global Clinical...mentioning
confidence: 99%
“…A total of 37 participants were recruited, who were part of the MBI held in a clinic for those with depression or anxiety symptoms (Takahashi et al, 2019(Takahashi et al, , 2020. The program organizer introduced the experiment to the MBI participants before the program started, and those interested in participating contacted the experimenter of this study.…”
Section: Participantsmentioning
confidence: 99%